PENGARUH BEBAN KERJA, KEPUASAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION TENAGA KESEHATAN BERSTATUS KONTRAK DI RSUD KOTA MATARAM - Rini Fitriantini; Agusdin Agusdin; Siti Nurmayanti (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
This study aims to analyze the effect of workload and job satisfaction on turnover intention, analyze the effect of workload and job satisfaction on work stress, and analyze the effect of work stress on turnover intention on contracted health workers in the Mataram City Regional General Hospital. Population of this study is all health workers with contract employment status on duty at the Mataram City General Hospital, amounting to 492 people with a total sample of 216 health workers determined based on the Isaac and Michael formula with an error rate of 5%. Collecting data in this study using survey research methods, data collection techniques using a questionnaire with a questionnaire with a Likert scale. Sampling techniques using Proportionate Stratified Random Sampling. This research uses structural equation modeling (SEM analysis) with AMOS software. The results showed that workload and work stress had a significant positive effect on turnover intention, workload had a significant positive effect on job stress, while job satisfaction had a significant negative effect on turnover intention and work stress. Hospital management is expected to pay attention to facilities and infrastructure in supporting work as well as guaranteeing safety and comfort in work so that health workers do not feel their workload is high and can reduce the level of turnover intention.